Development of an assessment tool for designated medical institutions in China——Based on the application of an online assessment system - Wang, Qian; Dai, Ruiming; Yu, Qianqian; Zhang, Tiantian; Wu, Bin (Frontiers in Public Health, 2024)
Background Due to the expanding coverage of medical insurance and the growth of medical expenses, the ability to assess the performance of designated medical institutions (DMIs) in supporting the delivery of high-quality patient care and the standardized use of funds represents a priority in China. Despite such interest, there has yet to be an operable standard and labor-saving method for assessing DMIs in China. Objective The main objectives include two aspects: (1) establishing an evaluation index system for DMIs based on contracts; (2) designing and developing an online evaluation platform. Methods A group of 20 experts with theoretical and practical expertise in medical insurance regulation and performance evaluation were invited to select available indicators. A combination weighting method based on analytic hierarchy process and entropy method was used to determine the weight coefficient. Shanghai was taken as the sample area, and 760 DMIs were included in the empirical research. The test-retest reliability method and criterion-related validity method was used to test the reliability and the validity of the evaluation result. Results An assessment index system that included 6 domains and 56 indicators was established in this study. Furthermore, we developed an online platform to assist in the implementation of the assessment. The results showed that the average score of assessment was 94.39, the median was 96.92. The test-retest reliability value was 0.96 (P ≤ 0.01), which indicated high stability of the assessment. In addition, there was a significant negative relationship between assessment score and the penalty amount of DMIs (R = −0.133, P < 0.001). After adjusting for the basic characteristics of medical institutions, the number of visits and revenue, the negative relationship was still significant (B = −0.080, P < 0.05). These results are consistent with expectations, indicating that the assessment had good criterion-related validity. Conclusions This study established an operable assessment measure and developed an online platform to assess the performance of DMIs. The results showed good feasibility and reliability in empirical research. Our research findings provided an operable Chinese solution for DMI assessment that saves manpower and time, which would have good enlightening significance in other regions of China and in low-income and middle-income countries internationally.